Pengaruh Good Corporate Governance (GCG), Modal Kerja, dan Solvabilitas Terhadap Profitabilitas Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2015 - Isma Wardani; Elsa Seri Indah Sitepu; Anggreini Roma Ito Purba; Delvi Anggriany Waruwu; Friska Darnawaty Sitorus (Forum Kerjasama Pendidikan Tinggi, 2020)
This study examines the effect of good corporate governance, solvency, working capital, on profitability to obtain profits in manufacturing companies listed on the Indonesia Stock Exchange in the period 2013-2015. This study uses a multiple linear regression model with a quantitative approach. The population of this study consisted of 143 manufacturing companies listed on the Indonesia Stock Exchange during the 2013-2015 period. There are 64 companies that meet the criteria to be used as research samples using themethod purposive sampling. This research results that good corporate governance, working capital and solvency simultaneously have a significant effect on profitability. Partially good corporate governance, working capital has a positive and significant effect on profitability. Solvency partially has a negative effect on profitability on manufacturing companies listed on the Indonesia Stock Exchange in the 2013-2015 period